Use of natural antioxidants in soybean biodiesel - Sousa, Leanne Silva de; Rodarte de Moura, Carla Veronica; Oliveira, Jose Eduardo de [UNESP]; Moura, Edmilson Miranda de (Elsevier B.V., 2014)
The antioxidant activity of curcumin and beta-carotene was studied as a method to control the oxidative process of methyl soybean biodiesel during a 180-day storage period. Initially, the antioxidant activity of curcumin and beta-carotene against radical 2,2-diphenyl-1-picrylhydrazyl (DPPH) was tested. Curcumin reduced the concentration of DPPH by 90% whereas beta-carotene reduced it by 15%. The antioxidant activity was determined through both the Rancimat and Petro-OXY methods. Results obtained from the two methods were consistent. They showed that curcumin increased the induction period of biodiesel by 83%, indicating the potential use of this antioxidant on an industrial scale. However, the study showed that beta-carotene acts as a pro-oxidant, reducing the induction period of biodiesel when subjected to the Rancimat and Petro-OXY tests. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Antioxidant activity; Curcumin; Biodiesel